2021
DOI: 10.1039/d0cp04647g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic deflection of neutral sodium-doped ammonia clusters

Abstract: A new Stern–Gerlach setup elucidates the spin relaxation dynamics of small weakly-bound Na(NH3)n clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…The effective magnetic moments μ eff of NaH 2 O (see Section ) and NaNH 3 (see ref ) are equal to the magnetic moment μ 0 of an m s = ±1/2 particle within our experimental uncertainty. All other clusters can be described with μ eff < μ 0 .…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The effective magnetic moments μ eff of NaH 2 O (see Section ) and NaNH 3 (see ref ) are equal to the magnetic moment μ 0 of an m s = ±1/2 particle within our experimental uncertainty. All other clusters can be described with μ eff < μ 0 .…”
Section: Resultssupporting
confidence: 53%
“…These deviations of experiment and simulation again show that the magnetic properties of the investigated clusters cannot be described by the magnetic moment of m s = ±1/2 particles. For Na(NH 3 ) n (see ref 43) and Na(H 2 O) n (see Section 3.1), we noted that an increase in cluster size, n, was correlated with a decrease in the experimentally observed deflection, γ d . Similar cluster-size-dependent deflection behavior is observed for Na(MeOH) n .…”
Section: Magnetic Deflection Of Na(hmentioning
confidence: 73%
See 1 more Smart Citation
“…The unique properties of solvated or weakly bound electrons have always been the focus of chemical research and utilization. The discovery of solvated electrons (e – sol ) dates back to the nineteenth century when experimental investigations showed that alkali metals dissolving in the gaseous or liquid ammonia exhibit e – sol characters for the first time . From then on, metal–ammonia complexes have been well-explored for ages on account of the excellent coordinating and electron-solvating abilities of ammonia molecules . Electrons of metal atoms deviate from the cation cores due to the repulsion from the lone pairs of the coordinating N and finally diffuse outside to the edge of the peripheral ligands, forming solvated electron precursors or presolvated electrons (e – pre ) in which the electrons are weakly bound. Undoubtedly, the external ligands have considerable impact on the electronic structures of metal atoms and chemical bonds of the polymetal molecules surrounded by solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to water cluster anion studies, , TRPES studies of larger, neutral clusters cannot exploit the full potential of cluster studies because cluster size selection is generally not possible for the latter. Size selection of neutral clusters is still limited to small clusters (e.g., by using inhomogeneous electric , and magnetic fields), and the same holds for photoelectron–photoion coincidence studies. , Thus, PES of larger, neutral clusters represents the average behavior of a broad cluster size distribution. However, progress in the measurement of size distributions of neutral clusters makes it now possible to determine the accurate average cluster size and width of the distribution. …”
Section: Introductionmentioning
confidence: 99%